2020
DOI: 10.3390/molecules25020358
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in Breast Cancer—Clinical and Preclinical Research Insights

Abstract: The Androgen Receptor (AR) is emerging as an important factor in the pathogenesis of breast cancer (BC), which is the most common malignancy among females worldwide. The concordance of more than 70% of AR expression in primary and metastatic breast tumors implies that AR may be a new marker and a potential therapeutic target among AR-positive breast cancer patients. Biological insight into AR-positive breast cancer reveals that AR may cross-talk with several vital signaling pathways, including key molecules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 46 publications
1
98
1
2
Order By: Relevance
“…Given these data, we consider it is important to correlate the blood androgen levels with the positivity of the AR, moreover the association between increased androgen levels and high BC risk in pre- and postmenopausal patients. We consider that this aspect may be taken into account for the screening of BC [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given these data, we consider it is important to correlate the blood androgen levels with the positivity of the AR, moreover the association between increased androgen levels and high BC risk in pre- and postmenopausal patients. We consider that this aspect may be taken into account for the screening of BC [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that AR is overexpressed in 10–41% of TNBCs [ 25 , 26 ]. However, the clinical and prognostic value of AR expression is still controversial [ 27 ], whereas few phase II studies have evaluated the clinical value of AR blockade in AR+ mTNBC, showing modest results [ 28 ]. Results from ongoing studies evaluating different AR blocking agents in early and mTNBC are still awaited [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR can also be activated in a ligand-independent manner through crosstalk with key signaling pathways, including PI3K/AKT and ERK (84). AR is involved in cell cycle regulation and the epithelial-to-mesenchymal transition (EMT) (85,86). AR has emerged as a new biomarker and a potential therapeutic target in TNBC.…”
Section: Myc and Cdkmentioning
confidence: 99%